Synthesis, Structural Calculations and Molecular Docking Studies of a Novel Uracil Derived Organic Molecule - Koz, Gamze (My University, 2018)
Anovel uracil derived compound, (E)-5-((3-chloro-2-hydroxybenzylidene)amino) pyrimidine-2,4(1H,3H)- dione, was synthesized and characterized using spectroscopic techniques. The interaction of the molecule with DNA was explored using computational methods which revealed that the molecule could act as a groove binder. The physicochemical properties of the molecule such as frontier molecule orbitals and chemical reactivity parameters were also investigated.

Urasil türevi yeni bir bileşik, (E)-5-((3-klor-2-hidroksibenziliden)amino)pirimidin-2,4 (1H,3H)-dion, sentezlendi ve spektroskopik yöntemler kullanılarak yapı tayini gerçekleştirildi. Molekülün DNA ile olan etkileşimi, bilgisayar destekli yöntemler ile araştırıldı ve oluk bağlayıcı olarak davranabileceği belirlendi. Bileşiğin, molekül orbitalleri ve kimyasal reaktivite parametreleri gibi fizikokimyasal özellikleri incelendi.
Yeni Urasil Türevi Organik Bir Molekülün Sentezi, Yapısal Hesaplamaları ve Moleküler Modelleme Çalışmaları
Keywords: Biyoloji; Mühendislik, Kimya